302 Impact of right ventricular pacing in patients with TAVI underwent permanent pacemaker implantation: the Pace-TAVI International Multicentre Study. (8th December 2021) - Bruno, Francesco; Ascenzo, Fabrizio D'; Muñoz-Pousa, Isabel; Saia, Francesco; Vaira, Matteo Pio; Baldi, Enrico; Leone, Pier Pasquale; Cabanas-Grandio, Pilar; Corcione, Nicola; Spinoni, Enrico; Annibali, Gianmarco; Russo, Caterina; et al.
Abstract: Aims: Permanent pacemaker implantation after transcatheter aortic valve implantation (TAVI) has emerged as a relevant issue, being more frequent than after surgery and the progressive shift towards low-risk patients stressed the importance to reduce the risk of complications that could impact patient's long-term prognosis. Long-term right ventricular pacing has been related to an increased risk of electromechanical asynchrony, negative left-ventricular remodelling, atrial fibrillation and heart failure, but there is a lack of evidence regarding the prognostic impact on TAVI patients. The aim of this international multicentre study is to assess the impact of right ventricular pacing on prognosis of TAVI patients undergone pacemaker implantation after the procedure due to conduction disorders. Methods and results: All the consecutive patients with severe aortic stenosis treated with TAVI and subsequently underwent pacemaker implantation in each participating centre were enrolled. Patients were divided into two subgroups according to the percentage of ventricular pacing (VP cut-off: 40%) at pacemaker interrogation. The primary endpoint was the composite of cardiovascular mortality and hospitalization for heart failure in subgroups based on the percentage of ventricular stimulation. All cause and cardiovascular mortality in the subgroups according to the percentage of ventricular pacing were the secondary endpoints. In total, 427 patients were enrolled, 153 patients with VP < 40% and 274 with a with VP ≥ 40%. Patients with VP ≥ 40% were older (81.16 ± 6.4 years vs. 80.51 ± 6.8 years), with higher NYHA class, a lower EF (55.26 ± 12.2 vs. 57.99 ± 11.3 P = 0.03), an increased end diastolic ventricular volume (112.11 ± 47.6 vs. 96.60 ± 40.4, P = 0.005) and diameter (48.89 ± 9.7 vs. 45.84 ± 7.5 P = 0.01). A higher incidence of moderate post-procedural paravalvular leak was observed in patients with VP ≥ 40% (37.5% vs. 26.85%, P = 0.03). Ventricular pacing ≥40% was associated with a higher incidence of the composite primary endpoint of CV mortality and HF hospitalization ( p at log rank test = 0.006, adjusted HR: 2.41; 95% CI: 1.03–5.6; P = 0.04). Patients with ventricular pacing ≥ 40% had also a higher risk of all-cause ( p at log rank test = 0.03, adjusted HR = 1.57; 95% CI: 1.03–2.38; P = 0.03) and cardiovascular ( p at log ank test =0.008, adjusted HR: 3.77; CI: 1.32–10.78; P = 0.006) mortality compared to patients with a VP < 40%. Conclusions: TAVI Patients underwent permanent pacemaker implantation after the procedure due to conduction disorders and with a VP ≥ 40% at follow-up are at increased risk of cardiovascular death and HF hospitalizations and of all-cause mortality compared to patients with a VP < 40%. It is mandatory to reduce the percentage of ventricular pacing at follow-up when possible or consider left ventricular branch pacing and biventricular pacing in TAVI patients.